2011
DOI: 10.1111/j.1365-2699.2011.02667.x
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up from epidemiology to biogeography: local infection patterns predict geographical distribution in fish parasites

Abstract: Aim  We investigated how the spatial distribution of parasites, measured as either their geographical range size or their frequency of occurrence among localities, relates to either their average local abundance or the variance in their abundance among localities where they occur. Location  We used data on the abundance of 46 metazoan parasite species in 66 populations of threespine sticklebacks, Gasterosteus aculeatus, from Europe and North America. Methods  For each parasite species, frequency of occurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 50 publications
(85 reference statements)
2
18
0
Order By: Relevance
“…Typically, species with high local abundance are more widely distributed across localities in any environment. The same pattern applies to parasite communities investigated to date (Barker et al , Cone et al , Poulin et al , Thieltges et al ). Different causal pathways have been proposed to explain this common pattern.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Typically, species with high local abundance are more widely distributed across localities in any environment. The same pattern applies to parasite communities investigated to date (Barker et al , Cone et al , Poulin et al , Thieltges et al ). Different causal pathways have been proposed to explain this common pattern.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, long distance transport of invertebrates via water birds could also promote sporadic movement of parasites in their intermediate hosts across water bodies. Parasites constrained to freshwater habitats may then be subjected to sporadic dispersal in which locally abundant species have an advantage (Poulin et al ) by having a higher chance of acting as source of colonisers to new localities in a metapopulation context. In addition, Poulin et al () found that species with high occupancy also have more variable local abundances, suggesting they can maintain populations through a larger range of different environments.…”
Section: Discussionmentioning
confidence: 99%
“…Logue et al (2011) argued that mass eff ects and species sorting cannot be distinguished without direct measurement of dispersal. Similarly, Poulin et al (2012) found that generalist parasites had larger geographic ranges relative to specialist parasites in a fi sh -parasite system. In our study system, we found evidence that local niche factors were most important in determining metacommunity structure and species richness.…”
Section: Discussionmentioning
confidence: 88%
“…Despite our low sample numbers and limited sampling range, geographic variability in infection prevalence suggests parasite susceptibility to local conditions (Poulin et al 2012), and several possibilities could explain the observed patterns, as follows.…”
Section: Latitudinal Effects On Infection Prevalencementioning
confidence: 98%
“…Pathogen transmission can increase with higher densities and greater connectivity between hosts (Poulin et al 2012, Izhar & Ben-Ami 2015. Durvillaea species in Australia are known to transition from being a relatively rare intertidal element at Tathra (the northern range limit) to a dominant habitatforming species on rocky intertidal platforms in Tasmania (southern part of the species' range) (Millar 2007).…”
Section: Population Densitiesmentioning
confidence: 99%